Effectiveness of Ethanol Extract among Three Ganoderma Species From Lombok in Inhibition Growth of Candida albicans and Cryptoccocus neoformans - Fitria Rizka Hidayat; Sukiman Sukiman; Ernin Hidayati; Sarkono Sarkono; Bambang Fajar Suryadi; Faturrahman Faturrahman (Journal of Science and Science Education, 2020)
Candida albicans and Cryptoccocus neoformans are opportunistic pathogenic fungi that cause infectious diseases that are the world's biggest health problems. The use of antibiotics is one way to overcome the spread of the infection and cause microbial resistance. Ganoderma is one of the many macrophages found on Lombok's island, and studies of its antifungal activity have not been carried out. The purpose of this study was to determine the antifungal potential and the effect of different concentrations of ethanolic extracts of three Ganoderma species on C. albicans and C. neoformans. Ganoderma samples were obtained from Suranadi Taman Wisata Alam (TWA), Sesaot TWA, Tunak Mountain TWA, Kerandangan TWA, and Pusuk Forest. Ganoderma extraction was carried out by the maceration method using ethanol 95% solvent. The extract concentrations used are 20%, 40%, 60% and 80%. This research was conducted using the wells method with metronidazole as a positive control and 50% DMSO as a negative control. The parameter measured is the large diameter of the inhibition zone formed around the well. The results obtained are the three species of Ganoderma have antifungal activity against test fungi, and different levels of concentration affect inhibition. The amount of the inhibition zone is directly proportional to the high concentration of the extract. All three Ganoderma species are more effective in inhibiting the growth of C. neoformans compared with Candida albicans